Mapping the Return Migration: Estimating and Projecting Indian Emigrants from the Gulf Cooperation Council (GCC) - Suhail, Mohammad; Ravshanov, Alikul Xudoyberdiyevich; Lutfullo, Ibragimovich; Marufdjon, Usmanov; Kadirov, Murodillo (Faculty of Geography, Universitas Gadjah Mada, 2025)
This study examines the phenomenon of return migration among Indian migrants in the Gulf Cooperation Council (GCC) countries, with a focus on the period from 2002 to 2014. Drawing on data from various sources, including government reports and field surveys conducted from November 2018 to May 2019, the research provides valuable insights into the patterns, trends, and implications of return migration for India. The analysis reveals a significant surge in the number of Indian migrants returning from the GCC region during the specified period, with an estimated 3-4 million individuals expected to have repatriated to India. Factors driving this trend include changes in labour demand, economic conditions, and government policies in both India and the GCC countries. The study also highlights the challenges faced by returnees, such as reintegration into the Indian labour market, access to social services, and cultural adjustments. Despite these challenges, return migration presents substantial opportunities for India, including the transfer of skills, knowledge, and financial resources from the diaspora, as well as the potential for enhanced economic cooperation and development partnerships between India and the GCC countries. By understanding the dynamics of return migration and addressing the associated challenges, India can better leverage the potential of its diaspora for national development and prosperity. Received: 2024-09-04 Revised: 2024-10-05 Accepted: 2025-08-15 Published: 2025-08-19